Direct angiotensin AT2 receptor stimulation using a novel AT2 receptor agonist, compound 21, evokes neuroprotection in conscious hypertensive rats. - Claudia A McCarthy (Public Library of Science (PLoS), 2014)
Background In this study, the neuroprotective effect of a novel nonpeptide AT2R agonist, C21, was examined in a conscious model of stroke to verify a class effect of AT2R agonists as neuroprotective agents. Methods and results Spontaneously hypertensive rats (SHR) were pre-treated for 5 days prior to stroke with C21 alone or in combination with the AT2R antagonist PD123319. In a separate series of experiments C21 was administered in a series of 4 doses commencing 6 hours after stroke. A focal reperfusion model of ischemia was induced in conscious SHR by administering endothelin-1 to the middle cerebral artery (MCA). Motor coordination was assessed at 1 and 3 days after stroke and post mortem analyses of infarct volumes, microglia activation and neuronal survival were performed at 72 hours post MCA occlusion. When given prior to stroke, C21 dose dependently decreased infarct volume, which is consistent with the behavioural findings illustrating an improvement in motor deficit. During the pre-treatment protocol C21 was shown to enhance microglia activation, which are likely to be evoking protection by releasing brain derived neurotrophic factor. When drug administration was delayed until 6 hours after stroke, C21 still reduced brain injury. Conclusion These results indicate that centrally administered C21 confers neuroprotection against stroke damage. This benefit is likely to involve various mechanisms, including microglial activation of endogenous repair and enhanced cerebroperfusion. Thus, we have confirmed the neuroprotective effect of AT2R stimulation using a nonpeptide compound which highlights the clinical potential of the AT2R agonists for future development.